Virus-like particles containing a prefusion-stabilized F protein induce a balanced immune response and confer protection against respiratory syncytial virus infection in mice - Luo, Jin; Qin, Huan; Lei, Lei; Lou, Wange; Li, Ruitong; Pan, Zishu (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) is a serious respiratory pathogen in infants and young children worldwide. There are no licensed RSV vaccines available. In this study, we explored the stable prefusion conformation virus-like particles (Pre-F VLPs) as an RSV vaccine candidate. The RSV fusion (F) protein mutants were constructed to form stabilized Pre-F or postfusion (Post-F) configuration. VLPs containing Pre-F or Post-F protein were generated by recombinant baculoviruses (rBVs)-insect cell expression system. The assembly and immunological properties of Pre-F or Post-F VLPs were investigated. Pre-F and Post-F VLPs contained characteristically antigenic sites Ø and I of pre- and postfusion conformation, respectively. Following immunization of mice, Pre-F VLPs elicited an upregulatory IFN-γ, IL-2 and IL-10 and downregulatory IL-4 and IL-5 cytokines production. The high percentage of CD25+ Foxp3+ cells or low IL-17A-producing cells among CD4+ T cells were found in the lungs of mice vaccinated with Pre-F VLPs. Importantly, immunization with Pre-F VLPs induced a high level of RSV neutralizing antibody and a balanced immune response, which protected mice against RSV infection without evidence of immunopathology. Our results suggested that Pre-F VLPs generated from rBVs-insect cells represent a promising RSV vaccine candidate.